2013
DOI: 10.3346/jkms.2013.28.9.1293
|View full text |Cite
|
Sign up to set email alerts
|

Podoplanin, α-Smooth Muscle Actin or S100A4 Expressing Cancer-Associated Fibroblasts Are Associated with Different Prognosis in Colorectal Cancers

Abstract: The interactions between the tumor microenvironment and tumor cells determine the behavior of the primary tumors. Whether cancer-associated fibroblasts (CAF) have a tumor progressive or a protective role likely depends on the type of tumor cells and the CAF subpopulation. In the present study, we analyzed the prognostic significance of CAF subpopulations in colorectal cancer (CRC). CAF phenotypes were analyzed in 302 CRC patients by using antibodies against podoplanin (PDPN), α-smooth muscle actin (α-SMA), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 25 publications
4
46
0
Order By: Relevance
“…It has been demonstrated that α‐SMA is widely expressed in CAFs and associated with poor prognosis of patients in various types of cancers, including oral tongue squamous cell carcinoma, hepatocellular carcinoma, non‐small‐cell lung cancer, and colorectal carcinoma . In our study, it was found that majority of ICC (86/106) are characterized by α‐SMA expression in CAFs.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It has been demonstrated that α‐SMA is widely expressed in CAFs and associated with poor prognosis of patients in various types of cancers, including oral tongue squamous cell carcinoma, hepatocellular carcinoma, non‐small‐cell lung cancer, and colorectal carcinoma . In our study, it was found that majority of ICC (86/106) are characterized by α‐SMA expression in CAFs.…”
Section: Discussionsupporting
confidence: 50%
“…It has been demonstrated that α-SMA is widely expressed in CAFs and associated with poor prognosis of patients in various types of cancers, including oral tongue squamous cell carcinoma, hepatocellular carcinoma, nonsmall-cell lung cancer, and colorectal carcinoma. [35][36][37][38] In our study, it was found that majority of ICC (86/106) are F I G U R E 3 CAFs promote proliferation, migration, and invasion of cholangiocarcinoma cells in vitro. A, The growth of cholangiocarcinoma cells (HuCCT-1 and RBE) cultured with CAFs-conditioned medium (CAFs-CM) was greatly accelerated compared with cells cultured with normal fibroblasts-conditioned medium (NFs-CM) and 10% FBS medium, especially on day 3 (P < 0.001), day 4 (P < 0.0001), and day 5 (P < 0.0001).…”
Section: Discussionmentioning
confidence: 52%
“…c, there was a roughly 20% decrease in the percentage of PDGFR‐α‐positive (PDGFR‐α+) fibroblasts in Braf V600E ; Pten lox5/lox5 ‐bcat/Fb tumors. Next, we evaluated the expression of α‐smooth muscle actin (α‐SMA), which has been found to be a specific CAF marker within solid tumors (Augsten, ; Choi et al., ; Huet et al., ; Tsukamoto, Mishima, Hayashibe, & Sasase, ). α‐SMA expression was markedly reduced (60%) in Braf V600E ; Pten lox5/lox5 ‐bcatFb tumors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pten lox5/lox5 -bcat/Fb tumors. Next, we evaluated the expression of α-smooth muscle actin (α-SMA), which has been found to be a specific CAF marker within solid tumors (Augsten, 2014;Choi et al, 2013;Huet et al, 2008;Tsukamoto, Mishima, Hayashibe, & Sasase, 1992). α-SMA expression was markedly reduced (60%) in Braf V600E ;…”
Section: Ecm Microenvironment Is Remodeled In Braf V600e ; Pten Loxmentioning
confidence: 99%
“…They have an established biological impact on tumorigenesis as matrix synthesizing or matrix degrading cells and play a critical role in cancer aggressiveness and metastasis [8] [9]. α-SMA and S100A4 expressions are recognized not only in the TAFs but also in smooth muscle cells, thus suggesting limitations for interpretation of their stromal positivity [10] [11].…”
Section: Discussionmentioning
confidence: 99%